2020
DOI: 10.1021/acsaem.0c00195
|View full text |Cite
|
Sign up to set email alerts
|

All-Inorganic CsPbBr3 Nanocrystals: Gram-Scale Mechanochemical Synthesis and Selective Photocatalytic CO2 Reduction to Methane

Abstract: Halide perovskite CsPbBr 3 has recently gained wide interest for its application in solar cells, optoelectronics and artificial photosynthesis, but further progress is needed to develop greener and more scalable synthesis procedures and for their application in humid environments. Herein, we report a fast and convenient mechanochemical synthesis of CsPbBr 3 perovskite nanocrystals with control over crystal size and morphology. These perovskite

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 73 publications
3
67
0
Order By: Relevance
“…The improvement in photocatalytic performance was attributed to the enhanced electron‐extraction ability of GO in the CsPbBr 3 QD/GO composite, confirmed by PL and photoelectrochemical impedance experiments. Following, Eslava and coworkers reported a facile and green mechanochemical approach to synthesize CsPbBr 3 nanocrystals with controlled crystalline size and tunable morphology by changing the reaction conditions such as milling time, ball size, and Cs precursor 85 . Furthermore, the photocatalytic experiments demonstrated that all these CsPbBr 3 nanocrystals showed good photocatalytic CO 2 reduction performance with CO (2.25 ± 0.09 μmol g −1 hour −1 ) as the major product accompanied with minor CH 4 (0.43 ± 0.03 μmol g −1 hour −1 ) and H 2 (0.08 ± 0.02 μmol g −1 hour −1 ) under simulated sunlight illumination.…”
Section: Photocatalytic Applications Of Halide Perovskite Compositesmentioning
confidence: 99%
“…The improvement in photocatalytic performance was attributed to the enhanced electron‐extraction ability of GO in the CsPbBr 3 QD/GO composite, confirmed by PL and photoelectrochemical impedance experiments. Following, Eslava and coworkers reported a facile and green mechanochemical approach to synthesize CsPbBr 3 nanocrystals with controlled crystalline size and tunable morphology by changing the reaction conditions such as milling time, ball size, and Cs precursor 85 . Furthermore, the photocatalytic experiments demonstrated that all these CsPbBr 3 nanocrystals showed good photocatalytic CO 2 reduction performance with CO (2.25 ± 0.09 μmol g −1 hour −1 ) as the major product accompanied with minor CH 4 (0.43 ± 0.03 μmol g −1 hour −1 ) and H 2 (0.08 ± 0.02 μmol g −1 hour −1 ) under simulated sunlight illumination.…”
Section: Photocatalytic Applications Of Halide Perovskite Compositesmentioning
confidence: 99%
“…This material showed signicantly improved activity for CO 2 photoreduction to CH 4 with a selectivity of 98.5% on an electron basis and a remarkable apparent quantum efficiency of 1.1% at 523 nm with water as a proton source. 18 Unfortunately, the well-known toxicity of Pb cations does not comply with sustainable design principles, hampering their development and application.…”
Section: Introductionmentioning
confidence: 99%
“…However, the present Bi catalyst can induce CO 2 -to-CO conversion with a relatively high CO evolution rate of 283.8 μmol g −1 h −1 under low-intensity LED light illumination (108.6 mW cm −2 , around solar intensity). Moreover, in comparison to most semiconductor systems coupled with plasmonic metals, the present catalytic circle for CO 2 reduction shows a higher photocatalytic activity, although some semiconductors with significantly high efficiencies were reported 1 , 4 , 29 , 38 , 39 . More details on the photocatalytic CO 2 reduction efficiencies on semiconductor systems can be found in the recent review articles 1 , 4 .…”
Section: Resultsmentioning
confidence: 68%